UNESCO Science Report 2021 - United Nations Educational, Scientific; Cultural Organization (United Nations, 2021)
It is striking how development priorities have aligned over the past five years. Countries of all income levels are prioritizing their transition to digital and ‘green’ economies, in parallel. This dual transition reflects a double imperative. On the one hand, the clock is ticking for countries to reach their Sustainable Development Goals by 2030. On the other, countries are convinced that their future economic competitiveness will depend upon how quickly they transition to digital societies. This seventh edition of the report monitors the development path that countries have been following over the past five years from the perspective of science governance. It documents the rapid societal transformation under way, which offers new opportunities for social and economic experimentation but also risks exacerbating social inequalities, unless safeguards are put in place.